2020
DOI: 10.1016/j.ijid.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and impact of occult hepatitis B virus, SEN virus, and torque teno virus in Egyptian hemodialysis patients with chronic hepatitis C virus infection

Abstract: Egypt ranks first regarding the prevalence of hepatitis C virus (HCV) infection. Many patients have concomitant diseases like kidney disorders requiring hemodialysis, a procedure carrying the hazard of transmitting other hepatitis viruses. The purpose of this study was to investigate for occult hepatitis B virus (HBV), SEN virus (SENV), and torque teno virus (TTV) among chronic HCV patients on maintenance hemodialysis to identify their impacts. Methods: A total of 325 hemodialysis patients were enrolled and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The estimated serological prevalence of co-infection between HBV and HCV ranges from 5% to 10% In general population and from 2% to 10% in positive HCV cases with detected RNA (Abdelaal et al, 2019;Caccamo et al, 2014;Lee, Hsu, et al, 2018). Some studies have found a high prevalence (22%-87%) of OBI in patients infected with HCV (Almeida et al, 2019;Amer et al, 2020Amer et al, , 2019Raimondo et al, 2005;Torbenson & Thomas, 2002). This is concerning, since the presence of OBI in individuals co-infected with HCV could cause reactivation of HBV and increase the progression to cirrhosis and HCC (Chen et al, 2019;Lee & Kwon, 2013).…”
Section: Obi/hcv Co -Infection Hbv Reactivation and Its Clinical Comp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated serological prevalence of co-infection between HBV and HCV ranges from 5% to 10% In general population and from 2% to 10% in positive HCV cases with detected RNA (Abdelaal et al, 2019;Caccamo et al, 2014;Lee, Hsu, et al, 2018). Some studies have found a high prevalence (22%-87%) of OBI in patients infected with HCV (Almeida et al, 2019;Amer et al, 2020Amer et al, , 2019Raimondo et al, 2005;Torbenson & Thomas, 2002). This is concerning, since the presence of OBI in individuals co-infected with HCV could cause reactivation of HBV and increase the progression to cirrhosis and HCC (Chen et al, 2019;Lee & Kwon, 2013).…”
Section: Obi/hcv Co -Infection Hbv Reactivation and Its Clinical Comp...mentioning
confidence: 99%
“…The molecular mechanisms involved in the reactivation of HBV, especially OBI, in HCV co-infected patients undergoing HCV treatment are still not well defined. The main theory is that HBV is chronically suppressed by HCV infection, with alternating phases of dominance from one virus to the other, due to the ability of core HCV protein to suppress HBV replication (Amer et al, 2020;Fung et al, 2017;. Host genes and immune regulation can also mediate the inhibition of HBV in cases of OBI.…”
Section: Obi/hcv Co -Infection Hbv Reactivation and Its Clinical Comp...mentioning
confidence: 99%
“…The highest occurrence of OBI was noted among HCV‐infected patients, 51 and in those who undergo maintenance hemodialysis 52 . In Egypt, several studies have reported a high incidence of OBI among these classes of patients, ranging from a low rate at 4.1% to a high rate of 50.8% 53–57 …”
Section: Hbv/hepatitis D Virusmentioning
confidence: 99%
“…Also, the innumerable usefulness of hemodialysis for patients with renal failure. Those two procedures are considered majorsources for blood-borne infections, by different ways as the equipment, surfaces, and personnel, not only for HCV and HBV but also for SENV and TTV 3,9, 13 .…”
Section: Introductionmentioning
confidence: 99%